Student and Instructor Generated Open Educational Resources Compare Favorably to a Traditional Textbook. Issue 4 (11th June 2019) - Stovall, Jeremy P; Laird, Shelby G; Welford, Lana; Williams, Allison
Abstract: Open Educational Resources (OER) are freely available materials that can be used in courses and modified by instructors. We developed an online OER silviculture textbook (OT). Some sections of OT were developed by the instructor, whereas others were developed by students enrolled in a silviculture course and subsequently edited by the instructor. As a preliminary examination of the effectiveness and student preference of OT, we administered a knowledge assessment and survey to both freshman and junior-level forestry students. We compared OT to a highly respected textbook in the field, The Practice of Silviculture, 9th Edition (Smith et al. 1997 ). Based on this study, both resources performed similarly and were similarly preferred by students. Although there are a number of limitations to this preliminary study (small sample size, only conducted at a single university, formatting both sources as paper copies) and to OER (time-consuming to create, lack of funding, lack of peer review), our results support further exploration of OER for use in forestry courses.